2009
DOI: 10.1159/000245904
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Radiation Hybrids to Genome Mapping in Domestic Animals

Abstract: Radiation hybrid mapping has emerged in the end of the 1990s as a successful and complementary approach to map genomes, essentially because of its ability to bridge the gaps between genetic and clone-based physical maps, but also using comparative mapping approaches, between ‘gene-rich’ and ‘gene-poor’ maps. Since its early development in human, radiation hybrid mapping played a pivotal role in the process of mapping animal genomes, especially mammalian ones. We review here all the different steps involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 244 publications
2
19
0
1
Order By: Relevance
“…Only eight BAC contigs could not be uniquely oriented in this study, the largest of which was only 0.4 Mb in size. Such high resolution has been observed in many human and animal radiation hybrid maps before [21,27,29], but among plant studies reported to date only a resolution of ~0.2 Mb calculated on the number of obligate breaks for chromosome 1D of wheat [35] is close to the high resolution presented here.…”
Section: Discussionsupporting
confidence: 83%
“…Only eight BAC contigs could not be uniquely oriented in this study, the largest of which was only 0.4 Mb in size. Such high resolution has been observed in many human and animal radiation hybrid maps before [21,27,29], but among plant studies reported to date only a resolution of ~0.2 Mb calculated on the number of obligate breaks for chromosome 1D of wheat [35] is close to the high resolution presented here.…”
Section: Discussionsupporting
confidence: 83%
“…By taking advantage of the conservation of syntenies, optimal orders can be proposed [58,59], thus maximizing the information obtained as first proposed by Hitte et al [60,61]. Indeed in duck, a dense RH map combined with scaffold sequencing and comparison to the chicken sequence, should lead to an improved genome assembly.…”
Section: Resultsmentioning
confidence: 99%
“…However, these stocks provide limited resolution due to a large deletion size (average deletion bin is ~35 Mb) and the inability to order markers within a given bin [8]. Radiation hybrid (RH) mapping is a valuable alternative to recombination-based maps and has been adopted for scaffold assembly of numerous animal genomes [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Radiation hybrid mapping, in combination with recombination mapping, has contributed enormously towards whole genome physical analysis and sequence assembly of human and animal genomes [9,17]. However, there have been relatively few examples of using RH mapping in plants, which include maize [18,19], barley ( Hordeum vulgare L.; [20]), cotton ( Gossipium hirsutum L.; [21,22]), and wheat [8,14,23-25].…”
Section: Introductionmentioning
confidence: 99%